Comparative Proteomics of Ostreid Herpesvirus 1 and Pacific Oyster Interactions With Two Families Exhibiting Contrasted Susceptibility to Viral Infection - Leprêtre, Maxime; Faury, Nicole; Segarra, Amélie; Claverol, Stéphane; Degremont, Lionel; Palos-Ladeiro, Mélissa; Armengaud, Jean; Renault, Tristan; Morga, Benjamin (Frontiers in Immunology, 2021)
Massive mortality outbreaks affecting Pacific oysters (Crassostrea gigas) spat/juveniles are often associated with the detection of a herpesvirus called ostreid herpesvirus type 1 (OsHV-1). In this work, experimental infection trials of C. gigas spat with OsHV-1 were conducted using two contrasted Pacific oyster families for their susceptibility to viral infection. Live oysters were sampled at 12, 26 and 144 hours post infection (hpi) to analyze host-pathogen interactions using comparative proteomics. Shotgun proteomics allowed the detection of 7 viral proteins in infected oysters, some of them with potential immunomodulatoy functions. Viral proteins were mainly detected in susceptible oysters sampled at 26 hpi, which correlates with the mortality and viral load observed in this oyster family. Regarding the oyster proteome, more than 3,000 proteins of Pacific oysters and contrasted proteomic responses were observed between A- and P-oysters, sampled at different time points. Gene ontology (GO) and KEGG pathway enrichment analysis performed on significantly modulated proteins uncover the main immune processes (such as RNA interference, interferon-like pathway, antioxidant defense) which contribute to the defense and resistance of Pacific oysters to viral infection. In the more susceptible Pacific oysters, results suggest that OsHV-1 manipulate the molecular machinery of host immune response, in particular the autophagy system. This immunomodulation may lead to weakening and consecutively triggering death of Pacific oysters. The identification of several highly modulated and defense-related Pacific oyster proteins from the most resistant oysters supports the crucial role played by the innate immune system against OsHV-1 and the viral infection. Our results confirm the implication of proteins involved in an interferon-like pathway for efficient antiviral defenses and suggest that proteins involved in RNA interference process prevent viral replication in C. gigas. Overall, this study shows the interest of multi-omic approaches applied on groups of animals with differing sensitivities and provides novel insight into the interaction between Pacific oyster and OsHV-1 with key proteins involved in viral infection resistance.